Treatment of advanced melanoma with laser immunotherapy and ipilimumab. Issue 5 (18th April 2017) - Naylor, Mark F.; Zhou, Feifan; Geister, Brian V.; Nordquist, Robert E.; Li, Xiaosong; Chen, Wei R.
Abstract: Immunotherapy has become a promising modality for melanoma, especially using checkpoint inhibitors, which revive suppressed T cells against the cancer. Such inhibitors should work better when combined with other treatments which could increase the number and quality of anti‐tumor T cells. We treated one patient with advanced (stage IV) melanoma, using the combination of laser immunotherapy (LIT), a novel immunological approach for metastatic cancers that has been shown to stimulate adaptive immunity, and ipilimumab. The patient was treated with LIT, followed with one course of ipilimumab 3 months after the beginning of LIT. After LIT treatment, all treated cutaneous melanoma in head and neck cleared completely. After the application of ipilimumab, all the tumor nodules in the lungs decreased. The patient had remained tumor free for one year. While anecdotal, the responses seen in this patient support the hypothesis that laser immunotherapy increases the number and quality of anti‐tumor T cells so that ipilimumab and other checkpoint inhibitors are more effective in enhancing the therapeutic effects.Picture : Schematic of treatment using laser immunotherapy and ipilimumab on a stage IV melanoma patient. Abstract : We developed a combination treatment regimen using laser immunotherapy (LIT) and ipilimumab to enhance the therapeutic effects for melanoma patient. Patient with advanced melanoma (chemotherapy resistant) were treated with LIT to stimulate an anti‐tumor immune response, followed by treatment with a T cell amplification drug, ipilimumab, to enhance the T cell response against tumor. Our experimental results indicate that LIT‐checkpoint inhibitor combintion may represent a major advancement in cancer immunotherapy.